Combined incentive actions, focusing on primary care professionals, to improve cervical cancer screening in women living in socioeconomically disadvantaged geographical areas: a study protocol of a hybrid cluster randomised effectiveness and implementation trial- RESISTE. Issue 11 (23rd November 2022) - Hassine, Amir; Antoni, Guillemette; Fender, Muriel; Slama, Katia; Léandri, François-Xavier; Fanon, Jean-Luc; Auvray, Christelle; Jaffar Bandjee, Marie Christine; Traversier, Nicolas; Fagour, Laurence; Rochaix, Lise; Fiorina, Camilla; et al.
Abstract : Introduction: Cervical cancer (CC) causes thousands of deaths each year. Nearly 100% of cases are caused by oncogenic strains of human papillomavirus (HPV). In most industrialised countries, CC screening (CCS) is based on the detection of HPV infections. For many reasons including lower adherence to CCS, underserved women are more likely to develop CC, and die from it. We aim to demonstrate that the use of incentives could improve screening rates among this population. Methods and analysis: Our cluster randomised, controlled trial will include 10 000 women aged 30–65 years eligible for CCS, living in deprived areas in four French departments, two mainlands and two overseas, and who did not perform physician-based HPV testing within the framework of the nationally organised screening programme. HPV self-sampling kit (HPVss) will be mailed to them. Two interventions are combined in a factorial analysis design ending in four arms: the possibility to receive or not a financial incentive of €20 and to send back the self-sampling by mail or to give it to a health professional, family doctor, gynaecologist, midwife or pharmacist. The main outcome is the proportion of women returning the HPVss, or doing a physician-based HPV or pap-smear test the year after receiving the HPVss. 12-month follow-up data will be collected through the French National Health Insurance database. We expect to increase the return rate of HPV self-samples by at least 10% (from 20% to 30%) compared with the postal return without economic incentive. Ethics and dissemination: Ethics approval was first obtained on 2 April 2020, then on July 29 2022. The ethics committee classified the study as interventional with low risk, thus no formal consent is required for inclusion. The use of health insurance data was approved by the Commission Nationale Informatique et Libertés on 14 September 2021 (ref No 920276). An independent data security and monitoring committee was established. The main trial results will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT04312178 .